Impact of Metaverse on Digital Marketing Strategy: An Experimental Study on Generation Z in Jakarta - Jaelani, Achmad; Purwanti, Winaya (Dinasti International Journal of Economics, Finance & Accounting, 2026)
This study analyzes the influence of metaverse usage on digital marketing strategies, with Generation Z serving as a mediating variable. The method employed is a quantitative approach through a questionnaire survey of 100 Generation Z students in Jakarta. Data were analyzed using Partial Least Squares (PLS) with tests of validity, reliability, coefficient of determination (R²), and path analysis. The findings indicate that metaverse usage significantly affects the effectiveness of digital marketing strategies. Generation Z acts as a partial mediator, meaning that although the characteristics of Generation Z strengthen the influence, the direct effect of the metaverse on marketing strategies remains dominant. The R² value of 53.3% for the Generation Z variable and 71.4% for the marketing strategy variable demonstrates the model’s strong explanatory capability. These findings affirm that integrating the metaverse into digital marketing strategies is a strategic step for companies to reach Generation Z consumers, who are highly familiar with technology, interactive, and value authentic experiences.